Building Assessment Post Earthquake 21 November 2022 in Cianjur District - Tampubolon, Sudarno P; Mulyani, Agnes Sri; Setyadi, Setyadi; Simanjuntak, Risma M (Asian Journal of Community Services, 2024)
The earthquake that occurred in the Cianjur area, West Java on Monday 21 November 2022 at 13.21 WIB resulted in 635 fatalities and 56,000 houses that were damaged. The results of the assessment found that many houses and public facility buildings still did not meet the requirements for earthquake-resistant buildings, especially in the use of concrete materials, main reinforcement, stirrups in columns, beams, foundations and beam-column joint, and did not have a strong column-weak beam planning concept. This can be seen from the inability of the column to withstand/ carry the working load which causes the column to collapse and damage. Therefore, it is very necessary to pay attention to building planning in Disaster Prone Areas (DPA) in accordance with earthquake resistant building regulations SNI 1726:2019 and SNI 2847:2019